Distribution of Reaction Sites in SOFC Cathode through Oxygen Isotope Labeling with Three-Dimensional Microstructural Analysis. Issue 6 (9th June 2021) - Nagasawa, Tsuyoshi; Shimura, Takaaki; Shikazono, Naoki; Hanamura, Katsunori
Abstract : Distribution of electrochemical reaction sites in a composite cathode of solid oxide fuel cell is investigated through active sites imaging by oxygen isotope labeling combined with three-dimensional microstructure observation by focused ion beam–scanning electron microscopy (FIB-SEM). Power generation with oxygen isotope and subsequent cell quenching is conducted at 973 K for LSM/YSZ cathode using a button cell. Through FIB-SEM observation and secondary ion mass spectroscopy (SIMS) analysis, the 3D microstructure of the quenched cathode with 2D 18 O concentration mapping in the middle plane of the characterized volume is obtained. Some LSM particles which show quite weak 18 O concentration are identified as the isolated phase, while several percolated LSMs near the electrolyte also show quite weak 18 O concentration, which indicates the existence of inactive reaction sites or ion/electron paths even inside the percolated phases. In addition, the oxide ion flux incorporated from the cathode/electrolyte interface is estimated from the 18 O concentration profiles at two locations in the observed area. A clear difference between the calculated oxide ion fluxes at the two locations is observed, which is discussed with the distributions of percolated TPB density and YSZ volume fraction in terms of the effective reaction thickness.